Eksperimen Pembelajaran Matematika Dengan Strategi Brain Based Learning Dan Problem Based Learning Terhadap Hasil Belajar Ditinjau Dari Motivasi Belajar Siswa Kelas VII SMP Negeri 2 Banyudono Semester GasalTahun Pelajaran 2016/2017 - Yuli Istanti, Wahyuningtyas, Drs.Slamet H.W, M.Pd (2017)
ABSTRACT Wahyuningtyas Yuli Istanti /A410130126. EKSPERIMEN PEMBELAJARAN MATEMATIKA DENGAN STRATEGI BRAIN BASED LEARNING DAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR DITINJAU DARI MOTIVASI BELAJAR SISWA KELAS VII SMP NEGERI 2 BANYUDONO SEMESTER GASAL TAHUN PELAJARAN 2016/2017. Skripsi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Surakarta. Desember, 2016. The purpose of the research are to analyze: (1) the effect of learning strategies Brain Based Learning and Problem Based Learning on learning outcomes. (2) the effect student learning motivation for learning ourcomes. (3) the interaction between learning strategy Brain Based Learning and Problem Based Learning terms of motivation on learning outcomes. Type of the research quantitative with quassi experimental design. Sample were taken by Cluster random sampling of the population of all students of class VII SMP Negeri 2 Banyudono academic year 2016/2017. Data collection techniques by using questionnaires, tests and documentation. Before to the analysis, first tested the normality and homogeneity test. The hypotesistent use unvalance two way analysis of variance with α=5% . the result of this tudy showed: (1) there was the effect of learning strategies Brain Based Learning and Problem Based Learning on learning outcones. (2) there was not effect student learning motivation for learning outcomes. (3) there was not interaction between the learning strategies Brain Based Learning and Problem Based Learning and motivation on learning outcomes. Keywords: Brain Based Learning, learning outcomes, Problem Based Learning,student learning motivation